ARTIKEL BROMANCE REPRESENTATION IN JAVA CULTURE BACKGROUND MOVIE - SUNNY UMA HANANI; Nilla Reza (Metakom, 2019)
The research attempts to represent Bromance in Indonesian culture implicit in the Yowis Ben Movie. The research used a qualitative method, the semiotics of Rolands Barthes. In this reseacrh we found the fact that the concept of Bromance has actually entered Indonesian culture. This can be seen in the Yowis Ben Movie. Where in the movie there is a group of male teenagers who have a closeness both emotionally, to physically. So it can be interpreted that the closeness of relationships between men in Indonesia cannot always be related to homosexuals (gays). Therefore, with this research we hope that in the future this research can increase literacy and knowledge to the people of Indonesia about the bromance relationship.